2001
DOI: 10.1002/ijc.10160
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin receptor p75NTR suppresses growth and nerve growth factor‐mediated metastasis of human prostate cancer cells

Abstract: The loss of tumor-and/or metastasis-suppressor gene function contributes to the transformation of human prostate epithelial cells to a malignant pathology. Such a putative tumor-suppressor and metastasis-suppressor gene(s) has been mapped to the region of 17q21, which coincidentally is in the vicinity of the human gene locus for the neurotrophin receptor p75 NTR . The p75 NTR is expressed in normal human prostate epithelial cells and exhibits an inverse association of p75 NTR expression with the malignant prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 35 publications
3
99
0
Order By: Relevance
“…15,[28][29][30][31] Among the targets that CASZ1 suppresses are the metastasis enhancers HGF and KITLG. 32,33 Preliminary studies have not identified a single critical target gene that mediates CASZ1 functions and current studies are aimed at delineating the targets and signaling pathways by which CASZ1 suppresses tumor growth and metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…15,[28][29][30][31] Among the targets that CASZ1 suppresses are the metastasis enhancers HGF and KITLG. 32,33 Preliminary studies have not identified a single critical target gene that mediates CASZ1 functions and current studies are aimed at delineating the targets and signaling pathways by which CASZ1 suppresses tumor growth and metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…These findings give further indirect evidence to the reported tumour/metastasis suppressor properties of NGFR. [7][8][9][10][11][12][13] Furthermore, studies addressing the prognostic impact of NGFR expression in basal-like carcinomas are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies in prostate and urothelial cancer suggest that NGFR may act as a tumour suppressor, negatively regulating cell growth and proliferation. [7][8][9][10][11][12][13] Previous studies on NGFR expression in breast carcinomas showed no direct association between the expression of this receptor and either diseasefree or overall survival. 14 However, the ratio between NGF:NGFR was reported to be of prognostic significance.…”
mentioning
confidence: 99%
“…In breast cancer and melanoma, p75NGFR acts as an oncogene, increasing cell proliferation, survival, and migration (6,(20)(21)(22). In contrast, in prostate cancer and neuroblastoma, p75NGFR acts as a tumor-suppressor gene, inducing apoptosis and inhibiting cell proliferation and invasion (23)(24)(25)(26)(27). Although p75NGFR is a conditional tumor suppressor in several types of cancers, the function of p75NGFR in colorectal cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The culture medium was changed every 24 hours. An equivalent concentration of DMSO was used in the control group.…”
Section: Cell Culture and 5-aza Treatmentmentioning
confidence: 99%